Efektifitas Pupuk Organik Cair Kulit Pisang dan Media Tanam Arang Sekam Padi Terhadap Pertumbuhan Bawang Merah (Allium Ascalonicum) - Fathul Hamdi Harahap; Hanifah Mutia Zaida Ningrum Amrul; Desi Sri Pasca Sari Sembiring (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Shallots (A. ascalonicum) are a horticultural commodity that has high economic value in Indonesia and is widely used, both as a cooking spice and traditional medicine. The purpose of this study was to determine the effect of banana peel POC and rice husk charcoal growing media on the growth of shallots and to assess whether there is an interaction between the two factors. The research activities were carried out in the experimental field of Panca Budi Development University located in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra Province at an altitude of 149 meters above sea level. The research implementation period was from November 2025 to January 2026. The method used was a 4x4 Factorial Randomized Block Design (RAK) with two factors resulting in 16 treatment combinations repeated in 3 blocks for a total of 48 plots. The first factor was Banana Peel POC with 4 levels, namely: F0 = Without POC, F1 = 100 ml/plot, F2 = 200 ml/plot, F3 = 300 ml/plot. The second factor of 4 Level Rice Husk Charcoal Planting Media is: H0 = Top Soil, H1 = Top Soil: Rice Husk Charcoal (3:1), H2 = Top Soil: Rice Husk Charcoal (1:1), H3 = Top Soil: Rice Husk Charcoal (1:3). The results of the study showed that the treatment of banana peel POC significantly affected the growth of shallot plants in plant height, number of leaves, number of tillers/sample, wet weight/sample, dry weight/sample and dry weight/plot, the best results in treatment F1 = 100 ml/plot. The treatment of rice husk charcoal planting media also significantly affected the growth of shallot plants in plant height, number of leaves, number of tillers/sample, wet weight/sample, dry weight/sample, but did not significantly affect the dry weight parameter/plot, the best results in treatment H1 = top soil: rice husk charcoal (1:3). There was no interaction between banana peel POC and rice husk charcoal planting media on the growth of shallots (A. ascanolicum).